Determination of Cd(II) and Cd-metallothioneins in biological extracts using baker's yeast and inductively coupled plasma optical emission spectrometry - Menegario, Amauri A.; Tonello, Paulo S.; Biscaro, Priscila A.; Brossi-Garcia, Ana L. (Springer, 2007)
The use of Saccharomyces cerevisiae as a sorbent material to separate Cd(II) and Cd-metallothionein complex (Cd-MT) has been explored. Solid-liquid phase extractions were carried out in batch mode and the main parameters of the process (pH, temperature, time of incubation, amount of biomass and analyte) were evaluated. Under optimized conditions, the yeast quantitatively retain (94 +/- 5%) the Cd(II) while 97 +/- 2% of the Cd-MT remain in the supernatant. on base of the findings of this study, a simple method is proposed to determine Cd(II) and Cd-MT in cytosols extracted from mouse kidney and crab hepatopancreas. Inductively coupled plasma optical emission spectrometry was used to quantify the analytes in solid and liquid phase. Determination of Cd in the solid phase was carried out by introducing a slurry of the yeast (0.0625 g/10 mL) directly to the inductively coupled plasma optical emission spectrometer. Mixed standards solutions, which also have been submitted to the extraction procedure, were used to quantify the analytes in the samples. Thus, matrix effects due to nebulization of the slurry were overcame. Limits of detection (3 sigma) for Cd(II) and Cd-MT were 1.5 and 1.2 mu g L-1, respectively. Relative standard deviations of signals were 4.2% for measurements in the slurry of solid phase and 2.1% for measurements in the liquid phase. Recoveries of the analytes in cytosol samples were between 76 and 114%. The concentrations of Cd(II) (2.4 +/- 0.5 mu g L-1) and Cd-MT (3.0 +/- 0.5 mu g L-1) found by using the proposed approach were close to those found by tangential-flow ultrafiltration technique (2.6 +/- 0.7 mu g L-1 for Cd(II) and 3.7 +/- 1.7 mu g L-1 for Cd-MT).
Keywords: Cd(II); Cd metallothioneins; Saccharomyces cerevisiae; fractionation; ICPOES